Diagnostic Accuracy of CSF and Blood Glucose Ratio in Diagnosis of Bacterial Meningitis in Children Using CSF Culture as Gold Standard - Afsheen Batool Raza, Muhammad Rizwan Safder, Novera Khalid (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find the diagnostic accuracy of CSF and blood glucose ratio in diagnosis of bacterial meningitis in children using CSF culture as gold standard. Study design: Cross sectional study Setting and duration: The study was conducted in the department of Pediatric Emergency Medicine, The Children’s Hospital and the Institute of Child Health, Lahore, from 15 May 2021 to 15 February 2022. Methods: A total of 140 children aged 1 month up to 14 years with clinical features suggestive of meningitis was selected. The patients underwent a lumbar puncture after getting consent from parents. The emergency laboratory examinations performed for their predictive value for bacterial meningitis as follows: CSF total cell count, CSF mononuclear cell count, CSF polymorphonuclear cell count, CSF polymorphonuclear/total cell ratio, CSF glucose, CSF/blood glucose ratio. The treatment was then readily started as per protocol for the presumptive diagnosis. Results: Amongst 145 cases, 51.72%(n=75) were upto 6 years of age while 48.28%(n=70) were between 7-14 years of age, mean+sd was calculated as 6.58+3.15 years, 60% were male and 40%(n=58) were females, mean CSF/Blood glucose ratio was calculated as 0.31+0.08. The diagnostic accuracy of CSF and blood glucose ratio in diagnosis of bacterial meningitis in children using CSF culture as gold standard was recorded as 90.32%, 90.36%, 87.5%, 92.59% and 90.34% for sensitivity, specificity, positive predictive value, negative predictive value and accuracy rate. Conclusion: Through the findings of this study, we concluded that the diagnostic accuracy of CSF and blood glucose ratio in diagnosis of bacterial meningitis in children using CSF culture as gold standard is higher but needs its validation through some other local trials in absence of previous data. Keywords: Bacterial meningitis, CSF culture, CSF/blood glucose ratio, Diagnostic accuracy